Dynamics of mangrove species dominant area changes in Timbulsloko and Bedono, Demak - Zahra Safira Aulia; Rudhi Pribadi; Muhammad Helmi (Depik, 2023)
Mangrove forests in Timbulsloko and Bedono villages have very important benefits in minimizing abrasion, due to tidal flooding and land absorption in this area. A large number of people have planted mangroves to restore the function of mangrove forests in coastal areas which conducted by NGOs, students, government agencies, and awareness from local residents. This study aimed to determine the dynamics of mangrove area and mangrove species dominant area changes in 2016, 2018, 2020 and 2022 based on Sentinel-2 Satellite Imagery processing, and to analyze the dynamic changes based on geospatial analysis. The method used in this study is divided into two: satellite imagery data processing and field survey. The result showed that the area of mangrove species in Timbulsloko and Bedono increased from 2016 to 2022. In 2016 the area of mangroves was 140.04 ha, 159.57 ha in 2018, 171.05 ha in 2020, and 234.8 ha in 2022. The use of Sentinel 2 Satellite Imagery to map the distribution of mangrove species dominant produce overall accuracy of 84.62%. The mangrove species with the highest area are Avicennia marina followed by Avicennia alba, Rhizophora apiculata, and Rhizophora mucronate. The increase in this area of mangroves in this area is due to natural additions and artificial additions due to mangrove planting conservation by several parties and the awareness of the local residents to protect mangroves.Keywords:Mangrove SpeciesDynamicsCoastal AreaSentinel 2Remote Sensing